profile
Опубликовано - 2 месяца назад | По предмету Математика | автор Аноним

Упростите выражение: (2x+1)^2-4(x-3)(3+x)

  1. Ответ
    Ответ дан Голубев Яша
    Упростим выражение:
    (2 * x + 1) ^ 2 – 4 * (x - 3) * (3 + x) = (2 * x + 1) ^ 2 – 4 * (x - 3) * (x + 3) = (2 * x + 1) ^ 2 – 4 * (x ^ 2 - 3 ^ 2) = (2 * x) ^ 2 + 2 * 2 * x * 1 + 1 ^ 2 – 4 * (x ^ 2 - 9) = 4 * x ^ 2 + 4 * x + 1 – 4 * x ^ 2 - 4 * 9 = 4 * x ^ 2 + 4 * x + 1 – 4 * x ^ 2 - 36 = + 4 * x + 1 – 36 = 4 * х - 35;
    В итоге получили, (2 * x + 1) ^ 2 – 4 * (x - 3) * (3 + x) = 4 * х - 35.
    0



Топ пользователи


Hekady (
204)
shozavitya (
180)
znanija (
172)
Eveline (
52)